The effects of cigarette smoking extracts on cell cycle and tumor spread: novel evidence - Aldo Pezzuto; Fabrizio Citarella; Ivana Croghan; Giuseppe Tonini (Future Science OA)
Cigarette smoking is a major preventable risk factor for lung cancer, contributing to lung cancer progression and metastasis. Moreover, cigarette smoking correlates with increased metastasis frequency of pancreatic, breast and bladder cancer. The aim of this review was to examine the role of cigarette smoke extract in cell cycle and cancer progression. Clinical impact and the effects of cigarette smoke extract on carcinogenesis are discussed. 98 of the over 5000 chemicals in tobacco smoke are known carcinogens that can act on cancer genes such as K-RAS and p53. Through various mechanisms these compounds can activate molecules involved in the cell cycle, such as cyclins, and molecules involved in apoptosis and autophagy, such as Beclin-1 or LC3B. A search of the literature, including in vitro and in vivo studies, was carried out and the results summarized.